Complete mitochondrial genome of the common Pochard (Aythya ferina) from Ningxia Hui autonomous region, China - Hao Zhai; Dehuai Meng; Zongzhi Li; YuHui Si; Hongxian Yu; Liwei Teng; Zhensheng Liu (Mitochondrial DNA. Part B. Resources, 2022)
We determined the whole mtDNA genome of the Common Pochard (Aythya ferina) in the Ningxia Hui Autonomous Region, China. The complete mitochondrial genome is 16,599 bp in length and consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 1 control region (D-loop). The nucleotide composition is 29.34% A, 22.23% T, 15.66% G, and 32.77% C. Phylogenetic analysis results showed close genetic relationship between A. ferina and Aythya americana.